Analisis Opini Masyarakat Terhadap Jasa Transportasi Online Menggunakan Text Mining Classification - Santi (AMIK STIEKOM SUMATERA UTARA, 2025)
The rapid development of communication technology has brought about social changes in society. Many businesses have emerged by taking advantage of this development, one of which is the emergence of online motorcycle taxi services. The presence of Ojek Online has provided solutions and addressed various concerns of the public regarding public transportation services. Traffic congestion in the capital city and public safety concerns regarding public transportation have been addressed by the emergence of Ojek Online, which offers convenience and comfort to its users. The presence of Ojek Online, which applies appropriate communication technology at a time when the public needs safe transportation and can serve as a solution during traffic congestion, is the focus of this study, which is considered necessary to be constructed in this research. Moreover, the integration of transportation services with the sophistication of Internet technology has made it easier for the public to make bookings, know transportation rates, destination locations, and identify drivers, which is a new innovation in the transportation business world. By using the Innovation Diffusion Theory and a heuristic qualitative research approach on two of the largest online motorcycle taxi service providers in Indonesia, namely Grab Bike and PT Gojek Indonesia, this study provides an in-depth, comprehensive, and holistic understanding of the development of appropriate communication technology. The findings of this study will contribute concepts, particularly in the application of appropriate communication technology innovations that can bring about changes in the social system of society.